Passivation of Interfaces in Thin Film Solar Cells: Understanding the Effects of a Nanostructured Rear Point Contact Layer - Salomé, Pedro M. P. (2018)
project IF/00133/2015. CAPES (CAPES-INL 04/14), CNPq, ARCIGS-M project is acknowledged. M.J.M. acknowledges funding from FCT through the grant SFRH/BPD/115566/2016. ALTALUZ (Reference PTDC/CTM-ENE/5125/2014). European Project BET-EU (H2020-TWINN-2015, grant 692373). The NanoFabrication department at INL, namely Joao Gaspar and Helder Fonseca, are recognized for the help in the development of the nanopatterning process.